Performance Evaluation of Page Migration Scheme for NVRAM-Based Wireless Sensor Nodes - Yeonseung Ryu (International Journal of Distributed Sensor Networks)
A wireless sensor network consists of low-powered and multifunctional sensor nodes. Since each sensor node is operated by a battery, the energy management has become one of the critical design challenges in wireless sensor networks. Some recent studies have shown that DRAM-based main memory spends a significant portion of the total system power. In this paper, we studied a buffer management scheme for hybrid main memory that combines low-power nonvolatile RAM (NVRAM) and DRAM in order to reduce the energy consumption in a sensor node. Though NVRAMs consume less power than volatile memories, they have common problems in write performance. The proposed scheme employs the page migration technique in order to reduce the write operations on NVRAM part of hybrid main memory. We have performed simulation studies and showed that the proposed page migration scheme outperforms the legacy buffer management schemes in terms of the number of write operations on NVRAM.